Potential mechanisms underlying sleep disturbance in young people with borderline personality disorder features: an exploratory study - Claire A. Jenkins; Katherine N. Thompson; Christian L. Nicholas; Jessica A. Hartmann; Andrew M. Chanen (Borderline Personality Disorder and Emotion Dysregulation, 2022)
Abstract Background Sleep disturbance is common among young people (15–25 years) with features of borderline personality disorder (BPD). However, the mechanisms underlying sleep disturbance in BPD remain unknown. Understanding these underlying processes is essential to guide the development of sleep-improvement interventions and to optimise their efficacy through identifying beneficial treatment targets. This exploratory study aimed to investigate potential underlying mechanisms to inform future hypotheses, research development, and provide insight into potential treatment targets to improve sleep in young people with BPD. This study explored the indirect roles of emotion regulation difficulties, depression, anxiety and stress in the relationship between BPD features and sleep disturbance in young people. Methods Sleep was measured subjectively (self-report questionnaires) and objectively (10 days wrist actigraphy) in 40 young people with BPD features and 38 healthy young people. Participants also completed the Difficulties in Emotion Regulation Scale and the Depression, Anxiety and Stress Scale. Results Mediation analyses revealed that impulse control difficulties, limited emotion regulation strategies and anxiety indirectly affected the relationship between group (BPD vs. healthy) and subjective sleep disturbance in young people. Lack of emotional awareness and anxiety contributed to associations between group and objectively longer time in bed and bedtime variability, respectively. Conclusions These preliminary findings suggest that targeting emotional dysregulation (impulse control, strategies, emotional awareness) and anxiety might be beneficial for improving sleep in this population.